2008
DOI: 10.12702/1984-7033.v08n03a08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic progress in traits of yield, phenology and morphology of common bean

Abstract: -The genetic progress achieved by the research institutions that registered common bean cultivars in the State of Rio Grande do Sul between 1998 and 2005 was estimated in traits of yield, phenology and morphology of common bean, with the aim to orient future genetic breeding studies. A total of 75 genotypes were evaluated, in variable number in the seven years, in a random block design with three replications. Positive genetic gains were verified for the yield traits (grain yield and components), while negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 1 publication
0
22
0
1
Order By: Relevance
“…Similarly, Abeledo et al (2003) indicated that most cereals exhibited a trend to a relatively low yield increases during much of the first half of the 20 th century followed by a rapid rate of yield gains, due to both genetic and managements, during the second half. Ribeiro et al, (2008) also reported that the significant increment of number of pods plant -1 yr -1 but no alteration for the number of seeds pod -1 yr -1 in some seasons of the test period.…”
Section: Issn: 2354-2292mentioning
confidence: 88%
“…Similarly, Abeledo et al (2003) indicated that most cereals exhibited a trend to a relatively low yield increases during much of the first half of the 20 th century followed by a rapid rate of yield gains, due to both genetic and managements, during the second half. Ribeiro et al, (2008) also reported that the significant increment of number of pods plant -1 yr -1 but no alteration for the number of seeds pod -1 yr -1 in some seasons of the test period.…”
Section: Issn: 2354-2292mentioning
confidence: 88%
“…Improvements in grain yield and related traits in CB have been associated with the improvement of the number of seeds per plant and grain yield per day (Bezaweletaw et al 2006;Ribeiro et al 2008). Several studies showed that hybridization of interracial bean varieties had higher yield, particularly in crosses between Mesoamerican with Durango or Jalisco races (Beebe 2012).…”
Section: Grain Yield and Yield-related Traitsmentioning
confidence: 99%
“…The newly registered common bean cultivars present a genetic progress when comparing the older cultivars. The annual genetic gain observed for grain yield was from 0.72 to 1.10% in common bean grown in Brazil (RIBEIRO et al, 2008;FARIA et al, 2013FARIA et al, , 2014. This increase in grain yield has been followed by phenological, plant architecture, and yield potential modifications.…”
Section: Introductionmentioning
confidence: 97%
“…This increase in grain yield has been followed by phenological, plant architecture, and yield potential modifications. The new common bean cultivars development by different breeding programs have earlier flowering and cycle (RIBEIRO et al, 2008), present more resistance to lodging and upright plant architecture (FARIA et al, 2013, and greater number of pods per plant (RIBEIRO et al, 2008). It was also possible to verify that the common bean cultivars registered after 2005 presented higher grain yield, adaptation and production stability when comparing the older cultivars (BARILI et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%